Mechanisms of paeoniaceae action as an antidepressant - Guo, Wanxu; Yao, Xiaoxiao; Cui, Ranji; Yang, Wei; Wang, Lei (Frontiers in Pharmacology, 2023)
Paeoniflorin (PF) has been widely used for the treatment of depression in mice models, some Chinese herbal compound containing PF on treating depression, such as Xiaoyao San, Chaihu-Shugan-San, Danggui Shaoyao San etc. Many experiments are also verifying whether PF in these powders can be used as an effective component in the treatment of depression. Therefore, in this review the antidepressant effect of PF and its mechanism of action are outlined with particular focus on the following aspects: increasing the levels of monoamine neurotransmitters, inhibiting the HPA axis, promoting neuroprotection, enhancing neurogenesis in the hippocampus, and elevating levels of brain-derived neurotrophic factor (BDNF). This review may be helpful for the application of PF in the treatment of depression.